Status of Vulnerability in Wheat and Barley Producing States of India - Sendhil, Ramadas; Jha, Ankita; Kumar, Anuj; Singh, Satyavir; Kharub, Ajit (Journal of Cereal Research, 2017)
Yield sensitivity to the anomalies of weather is an emerging issue in the perspective of climate smart farming particularly in the vulnerable regions and is expected to have a negative effect on the crop productivity. An attempt has been made to track the vulnerable regions for wheat and barley against climate change based on the composite index estimation viz., sensitivity, exposure and adaptive capacity. Relevant variables under each category were chosen with utmost care and the weights were assigned through principal component analysis. Vulnerability is the outcome of skewed production processes which is a result of less adaptive capacity relative to the potential impact (sensitivity + exposure). The investigation alarmed that the central part of India is highly prone to vagaries in climate change. High vulnerable states having a considerable share in crop production should be given prime priority in framing policies targeting for minimization of losses considering the adaptation strategies practiced in least vulnerable regions like Punjab and Haryana. The adaptive measures should be region and farm specific followed by appropriate implementation of policies and investment plans. Â DOI:10.25174/2249-4065/2017/70082Â